High performance liquid chromatography for the detection and estimation of amino acids in relation to Fusarium wilt (panama disease) in banana - Danis Ponniah3, Irudayaraj. V4, Felcy Navajothy. A1*, Narayanaswamy. R2 (International Multidisciplinary Research Journal, 2012)
Panama disease of banana is an obnoxious disease caused by the fungal pathogen Fusarium oxysporum. The variation in the degree of susceptibility and resistivity depends upon several macronutrients, micronutrients, polyphenols and primary metabolites-carbohydrates, protein and lipids and free amino acids in the host. Studies on such relationships between free amino acids and host-pathogen interaction are limited in agricultural crops particularly on materials based on the traditionally cultivated land are scarce. In order to understand the role of free amino acids of the host-banana in relation to Fusarium-wilt disease, HPLC study was carried out in five susceptible (Healthy/Infected) and five resistant varieties of banana from Tirunvelveli district. The results show the quantitative difference in amino acids of susceptible-healthy, susceptible-infected and resistant varieties. Inter-varietal difference in quantity of various amino acids in each group of samples has also been observed. Except two amino acids, tyrosine and lysine, all the other 13 amino acids are present in maximum amount in the infected samples of Monthan and Nadu in which the healthy samples are with very low amount of amino acids. Lysine and tyrosine are present in maximum amount in healthy samples of Rasthali and Rasakathali respectively. Major change in the quantity of arginine is related with the production of Nitric Oxide, an important chemical related to disease resistance. Occurrence of enormous quantity of glutamic acid, an important cellular osmolyte, in infected sample has been attributed to the role in controlling water loss by controlling the stomatal movement and thus ultimately save the infected plant from wilting.